Reexamination of the spawning migration of Anguilla dieffenbachii in relation to water temperature and the lunar cycle. Issue 1 (2nd January 2020) - Watanabe, Shun; Higuchi, Takatoshi; Noshiro, Masaharu; Manabe, Ryotaro; Miller, Michael J.; Jellyman, Donald J.; Tsukamoto, Katsumi
ABSTRACT: The oceanic spawning migration of female Anguilla dieffenbachii eels was previously studied using pop-up satellite transmitting tags (PSAT). The swimming depths and experienced-temperature data of 3 eels released in May 2006 were re-examined in relation to water temperature data, and also lunar cycle and regional hydrography as these latter aspects were not considered in the original study. Eel 2 and Eel 3 initially experienced lower water temperature above 600 m, suggesting they remained south of the subtropical-convergence front longer than Eel 1. Their experienced nighttime minimum depths showed linear relationships with the lunar cycle, because they swam shallower during new moon than during full moon. The eels experienced narrow deep-day temperature ranges at a wide range of depths compared to experiencing narrow shallow-night depth ranges where temperatures varied more widely, indicating that several different factors determine their day and night depth ranges.